Body mass index and triceps skinfold thickness in prepubertal children in Slovenia - Planinšec, Jurij (Array, 2009)
Abstract: The main aim of this study was to analyze overweight and obesity in children on the basis of body mass index (BMI) and triceps skinfold thickness (TSF). The sample included 5,613 children, aged 6 to12 years (X=9.23; SD=1.69) from Slovenia. Children were classified as non-overweight, overweight and obese according to age and sex specific BMI cut-off points. The results show that 18.3% of boys and 18.5% of girls are overweight and 6.5% of boys and 6.7% of girls are obese. The correlation between BMI and TSF in boys (r=0.785) and girls (r=0.783) are almost equal. Body weight has a lower correlation with TSF in boys (r=0.691) and in girls (r=0.631). The c2 test show that there is a significant difference (p<0.001) in TSF according to weight status. The results show that TSF and weight status of prepubertal children are closely related and that the criterion for the determination of weight status on the basis of BMI is well defined